SOME REFLECTIONS OF THE SCOPE OF AUDITING. - Borth, Daniel; Winakor, Arthur H. (The Accounting Review, 1935)
Abstract When the growing conscious recognition of the importance of financial data in the ordering of everyday business and economic life, the need of basic economic facts is providing a constantly enlarging opportunity for the accounting profession. The early conceptions of the functions of the auditor were such as to confine him to the duties of a mere checker and verifier of debits and credits. As business became more complex in its interrelationships there has been a compensating broadening demand for the acceptance of new and formerly unrecognized responsibilities by the auditor. The control of business enterprises within and among themselves has emphasized the importance of the budgetary and managerial aspects of the accountants' reports in enabling business units to coordinate their internal and external activities in the scheme of the economic plan. The principles of auditing are partially adaptations from other fields; they are practices from other fields which it has been found feasible to incorporate into auditing procedure and routine, in the attempt to approach as closely as possible to a realistic presentation of dynamic facts.